2015
DOI: 10.1186/s12870-015-0511-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporal transcriptome profiling reveals expression partitioning of homeologous genes contributing to heat and drought acclimation in wheat (Triticum aestivum L.)

Abstract: BackgroundHexaploid wheat (Triticum aestivum) is a globally important crop. Heat, drought and their combination dramatically reduce wheat yield and quality, but the molecular mechanisms underlying wheat tolerance to extreme environments, especially stress combination, are largely unknown. As an allohexaploid, wheat consists of three closely related subgenomes (A, B, and D), and was reported to show improved tolerance to stress conditions compared to tetraploid. But so far very little is known about how wheat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
329
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 340 publications
(351 citation statements)
references
References 116 publications
17
329
1
4
Order By: Relevance
“…It is thought that homoeologs make unequal contributions to total gene expression levels in polyploid wheat and that gene expression is regulated in a complex manner during grain development, possibly due to crosstalk between genomes during polyploidization (Akhunova et al, 2010;Chagué et al, 2010;Leach et al, 2014;Liu et al, 2015;Han et al, 2016). In this study, a major proportion of homoeologous gene pairs (65.8%) indeed exhibited divergent expression patterns in terms of genomic imprinting in polyploid wheat.…”
Section: Interplay Among Subgenomes Might Influence Genomic Imprintinmentioning
confidence: 73%
“…It is thought that homoeologs make unequal contributions to total gene expression levels in polyploid wheat and that gene expression is regulated in a complex manner during grain development, possibly due to crosstalk between genomes during polyploidization (Akhunova et al, 2010;Chagué et al, 2010;Leach et al, 2014;Liu et al, 2015;Han et al, 2016). In this study, a major proportion of homoeologous gene pairs (65.8%) indeed exhibited divergent expression patterns in terms of genomic imprinting in polyploid wheat.…”
Section: Interplay Among Subgenomes Might Influence Genomic Imprintinmentioning
confidence: 73%
“…HD2329 showed 1.93-fold increase in the expression under HS of 30ºC for 1h.HD2985 during grain-filling showed expression of 2-fold in response to HS of 38ºC for 1 h. Similarly, HD2329 showed 1.75-fold increase in the expression in response to HS of 38ºC for 1 h. Pawlowicz et al, (2012) observed that increase in the accumulation of PsbO gene in Tall fescue (Festuca arundinacea) in response to drought stress. A significant, positive, and linear correlation has been reported by Liu et al, (2015) in which they have showed the increase in digital fold expression of PsbO gene under heat and drought stress in wheat. Choulet et al, (2014) also reported the increased digital expression of PsbO gene in different tissues of wheat.…”
Section: Expression Profiling Of Psbogene In Wheat Under Heat Stressmentioning
confidence: 89%
“…In addition, expression of transcript homologous to Arabidopsis Rap2.6L was significantly up-regulated in wheat in response to drought or heat stress applied individually, but not to the drought and heat stress combination. 31 Overexpression of Rap2.6L in Arabidopsis was shown to enhance tolerance to abiotic stresses via activating hormone signaling pathways involving ABA, JA, SA and ethylene. 32,33 These results suggest that, to some extent, regulatory mechanisms of hormone signaling pathways underlying tailored responses of plants to drought, heat and their combination might be different depending on plant species.…”
mentioning
confidence: 99%